Skötselmetoder för bestånd med produktions- och naturvårdsmål - Haraldsson, Martin (SLU/Southern Swedish Forest Research Centre, 2005)
This study is made on assignment by the local board of forestry in Skåne, Blekinge and Halland. The change of the forest law 1994 brought a new type of management plan. A more active planning was introduced in order to equate the environment goal with the production goal. The purpose with this study is to give a better picture of how planning for nature conservation in production forest is made and to develop support for selection of silviculture methods for stands with combined goals. With combined goals means production forestry with a reinforced consideration to both nature and culture, called PF-classified stands. This was done by: • Describing silviculture models from the literature that are possible to use for stands with combined goals. • Describing silviculture models that is used in practice in stands with combined goals. • Describing how the classification of stands with combined goals is used. Which means, were in the terrain, with which frequency and in which type of forest PF-classification is used. • Comparing differences and similarities of theoretical and practical used models. The study was done partly as a literature study and partly as an interview study of forest planners. These planners were active in Halland, Skåne and Blekinge. In order to get as large amount of data as possible planners from local board of forestry , Södra and Skogssällskapet were interviewed. Through the literature study a number of possible silviculture models were developed, for stands with combined goals. It resulted in singletree cutting, selective cutting, regeneration with shelterwood and stands with mixed tree species composition. The results from the analysis of the local forestry boards data shows that all tree-species apart from spruce occurs relatively more often in PF-stands than average. The interviews resulted in five main types of stands with combined goals. The stands are mixed noble deciduous tree, 8 %, older beech stands, 11 %, stand-zones, 14 %, shelterwood of pine, 18 % and production stands of spruce with specific natural or cultural objects 27%. There is an uncertainty among the interviewed forest planners how the different types with combined goals should be managed. They agree that the stands should be managed with continues cover forestry or regeneration under shelterwood. The exeption is spruce with specific natural or cultural objects. This stand type is still managed with traditionally spruce silviculture but with small areas of nature consideration to maintain the protection area.